Supervision Strategy of the Madrasah Principal in Improving Teacher Performance and Welfare - Hamzah, Akhmad Fauzi; Kholil, Mohammad (UII Darullughah Waddawah Pasuruan, 2024)
The improvement of national education quality is significantly influenced by the performance and welfare of educators, particularly within madrasah environments. This study aims to examine the leadership strategies of madrasah principals in enhancing teachers' performance and welfare at Madrasah Ibtidaiyah Pesantren Anak Sholeh Baitul Qur’an Gontor Ponorogo. The research employs a qualitative approach with data collection techniques including in-depth interviews, observation, and documentation, followed by inductive analysis. The findings reveal that the principal implements various efforts such as training, committee involvement, routine supervision, and collaboration with external institutions to improve teachers’ competencies and motivation. Additionally, the principal actively formulates welfare policies, both material and non-material, to foster a conducive work environment. This adaptive and participative leadership strategy proves effective in improving teachers’ performance and welfare, ultimately contributing to the enhancement of educational quality at the institution.